2007
DOI: 10.1016/j.meatsci.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of intramuscular, intermuscular and subcutaneous adipose tissues in yearling bulls of different genetic groups

Abstract: Fatty acid (FA) composition of intramuscular (IM, Longissimus thoracis muscle), intermuscular (IT) and subcutaneous (SC) fat of one hundred intensively fed yearling bulls with different propensities to fatten were studied. Meat samples were collected from Asturiana de los Valles bulls with different genotypes with respect to the myostatin gene (mh/mh n = 24, mh/+ n = 26 and +/+ n = 25) and from Asturiana de la Montañ a (n = 25) bulls lacking the mutation responsible for double muscling and characterised by sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
40
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 53 publications
20
40
0
3
Order By: Relevance
“…Significantly higher CLA content (0.404%) was seen in subcutaneous fat, which is consistent with the findings of Aldai et al (9), who compared 3 types of adipose tissue (subcutaneous, intramuscular, and intermuscular) in yearling bulls and reported that CLA content was highest in the subcutaneous fat (0.42%), followed by intermuscular fat (0.37%) and intramuscular fat (0.22%). According to Kazala et al (26) and Raes et al (4), whose findings are cited in the work of Aldai et al (9), the above could be due to the fact that CLA isomers are found mostly in the fraction of neutral lipids. Despite the lowest CLA content, intramuscular fat had significantly (P ≤ 0.01) higher concentrations of PUFAs than the other analyzed fats, both in our experiment and in the studies cited above.…”
Section: Discussionsupporting
confidence: 90%
“…Significantly higher CLA content (0.404%) was seen in subcutaneous fat, which is consistent with the findings of Aldai et al (9), who compared 3 types of adipose tissue (subcutaneous, intramuscular, and intermuscular) in yearling bulls and reported that CLA content was highest in the subcutaneous fat (0.42%), followed by intermuscular fat (0.37%) and intramuscular fat (0.22%). According to Kazala et al (26) and Raes et al (4), whose findings are cited in the work of Aldai et al (9), the above could be due to the fact that CLA isomers are found mostly in the fraction of neutral lipids. Despite the lowest CLA content, intramuscular fat had significantly (P ≤ 0.01) higher concentrations of PUFAs than the other analyzed fats, both in our experiment and in the studies cited above.…”
Section: Discussionsupporting
confidence: 90%
“…The type of animals used in the present study ('Asturiana de los Valles') were very lean as previously reported (Aldai et al, 2007a;Martínez et al, 2010). This cattle breed has a mutation in the bovine myostatin gene that is responsible for PUFA 5 polyunsaturated fatty acid; HUFA 5 highly unsaturated fatty acids; P/s 5 polysaturated/saturated; unk 5 unknown position of double bonds.…”
Section: Discussionmentioning
confidence: 76%
“…For instance, in the 'Asturiana de los Valles' breed from northern Spain, the frequency of animals exhibiting doubled muscling has increased over the last decade to the point now where most of the animals of this breed are genetically homozygous (mh/mh) or heterozygous (mh/1) for the gene responsible for muscular hypertrophy (Grobet et al, 1998;Pé rez, 2005). Consequently, the beef obtained is very lean and the fatty acids profile can be affected (Aldai et al, 2007a and2007b). A high fat content in muscle is associated with -Present address: Instituto de Ganadería de Montañ a, CSIC-ULE, Finca Marzanas, 24346 Grulleros, Leó n, Spain.…”
Section: Introductionmentioning
confidence: 99%
“…소의 지방축적은 근내지방이 마지막으로 축적되고 (Harper and Pethick, 2004), 도체의 육질등급이 좋을수록, 육량등급 이 낮아지는 상반되는 특성이 있고 (Smith and Oltgen, 1996), 도체의 등지방두께 증가에 따른 육질등급의 향상에는 한계 가 있으며 (Brethour, 2004), 맛에 영향을 주는 근내지방과 같 은 축적부위가 중요하나 (Aldei et al, 2007) 도체의 등지방두 께는 근내지방과 유전적 상관관계가 낮고 (Nogi et al, 2010) 체지방과 상관관계가 높다고 하였다 (Brethour, 2004). 또한, 도체의 가치평가에서 지방에 의한 손실이 76%이며 (Smith and Oltgen, 1996), 출하우의 등지방이 4 mm 이하 및 14 mm 이상일 때 소득 감소가 가장 크다고 하였다 (Amer et al, 1994).…”
unclassified